Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's solve the problem step by step.
We are given two functions:
[tex]\[ f(x) = 3x^2 - 1 \][/tex]
[tex]\[ g(x) = -2x + 7 \][/tex]
And we need to calculate [tex]\( f(x) + g(x) - 3 \)[/tex] for a particular value of [tex]\( x \)[/tex]. In this case, [tex]\( x = 3 \)[/tex].
First, let's find [tex]\( f(x) \)[/tex] when [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = 3(3)^2 - 1 \][/tex]
[tex]\[ f(3) = 3 \cdot 9 - 1 \][/tex]
[tex]\[ f(3) = 27 - 1 \][/tex]
[tex]\[ f(3) = 26 \][/tex]
Next, let's find [tex]\( g(x) \)[/tex] when [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = -2(3) + 7 \][/tex]
[tex]\[ g(3) = -6 + 7 \][/tex]
[tex]\[ g(3) = 1 \][/tex]
Now, we can calculate [tex]\( f(3) + g(3) - 3 \)[/tex]:
[tex]\[ f(3) + g(3) - 3 = 26 + 1 - 3 \][/tex]
[tex]\[ f(3) + g(3) - 3 = 27 - 3 \][/tex]
[tex]\[ f(3) + g(3) - 3 = 24 \][/tex]
Therefore, the answer is not one of the given options. Let's revisit the answer choices to confirm.
\- 39
\- 27
\- -14
\- -41
Since 24 is not among the provided options, it is likely that there was an error either in the problem's question or in the provided answer choices. The correct calculation, however, yields:
[tex]\[ \boxed{24} \][/tex]
We are given two functions:
[tex]\[ f(x) = 3x^2 - 1 \][/tex]
[tex]\[ g(x) = -2x + 7 \][/tex]
And we need to calculate [tex]\( f(x) + g(x) - 3 \)[/tex] for a particular value of [tex]\( x \)[/tex]. In this case, [tex]\( x = 3 \)[/tex].
First, let's find [tex]\( f(x) \)[/tex] when [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = 3(3)^2 - 1 \][/tex]
[tex]\[ f(3) = 3 \cdot 9 - 1 \][/tex]
[tex]\[ f(3) = 27 - 1 \][/tex]
[tex]\[ f(3) = 26 \][/tex]
Next, let's find [tex]\( g(x) \)[/tex] when [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = -2(3) + 7 \][/tex]
[tex]\[ g(3) = -6 + 7 \][/tex]
[tex]\[ g(3) = 1 \][/tex]
Now, we can calculate [tex]\( f(3) + g(3) - 3 \)[/tex]:
[tex]\[ f(3) + g(3) - 3 = 26 + 1 - 3 \][/tex]
[tex]\[ f(3) + g(3) - 3 = 27 - 3 \][/tex]
[tex]\[ f(3) + g(3) - 3 = 24 \][/tex]
Therefore, the answer is not one of the given options. Let's revisit the answer choices to confirm.
\- 39
\- 27
\- -14
\- -41
Since 24 is not among the provided options, it is likely that there was an error either in the problem's question or in the provided answer choices. The correct calculation, however, yields:
[tex]\[ \boxed{24} \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.